Regulating the risk of unemployment national adaptations to post-industrial labour markets in Europe - Clasen, Jochen; Clegg, Daniel (Oxford : Oxford University Press, 2011)
'Regulating the Risk of Unemployment' offers a systematic comparative analysis of reforms to unemployment protection systems in European countries since the early 1990s. The volume sheds new light on important changes in a core field of welfare state activity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Unemployment insurance -- Europe; Public welfare -- Europe